Multidimensional model for the circular economy in manufacturing companies (2025)
The successful implementation of the circular economy (CE) is expected to lead companies to improve their sustainability performance to support the transition to a more desirable economic system. However, the body of knowledge and evidence on the effect of the CE on sustainability performance shows fragmented and, in some cases, contradictory results. For instance, empirical evidence from some research has indicated that the adoption of certain CE practices has not had positive or significant effects on sustainability performance of manufacturing firms in different countries. Moreover, from a practical perspective, it has been shown that professionals receive little guidance on the effective implementation of the CE in their companies, which results in a high failure rate during its adoption and difficulties in achieving environmental, social, and economic benefits.